2006
DOI: 10.1007/s00269-006-0066-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Fe among octahedral sites and its effect on the crystal structure of pumpellyite

Abstract: Two pumpellyites with the general formula W 8 X 4 Y 8 Z 12 O 56-n (OH) n were studied using 57 Fe Mo¨ssbauer spectroscopic and X-ray Rietveld methods to investigate the relationship between the crystal chemical behavior of iron and structural change. The samples are ferrian pumpellyite-(Al) collected from Mitsu and Kouragahana, Shimane Peninsula, Japan. Rietveld refinements gave Fe(X):Fe(Y) ratios (%) of 41.5(4):58.5(4) for the Mitsu pumpellyite and 46(1):54(1) for the Kouragahana pumpellyite, where Fe(X) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 27 publications
10
25
0
Order By: Relevance
“…Both bond valence calculations and located hydrogen sites indicated that the O5, O7, O10 and O11 positions represent hydroxyl groups. The bond -valence result is consistent with previous studies Donnay, 1971, 1973;Yoshiasa and Matsumoto, 1985;Nagashima et al, 2006;.…”
Section: Crystal Structural Solution and Refinementssupporting
confidence: 82%
See 1 more Smart Citation
“…Both bond valence calculations and located hydrogen sites indicated that the O5, O7, O10 and O11 positions represent hydroxyl groups. The bond -valence result is consistent with previous studies Donnay, 1971, 1973;Yoshiasa and Matsumoto, 1985;Nagashima et al, 2006;.…”
Section: Crystal Structural Solution and Refinementssupporting
confidence: 82%
“…The refined site occupancies of cations determined here are also similar to those of is not yet known. Nagashima et al (2006) and found a positive correlation between the mean Y -O distance and mean ionic radius of the Y site, but no correlation between mean X -O and the mean ionic radius of the X site. They concluded that the cation substitution at the Y site directly results in structural change.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrothermal alteration of the Kouragahana dolerite is characterized by the mineral assemblages of Ferich pumpellyite + prehnite and of prehnite + babingtonite in veins and cavities. The former assemblage indicates low -temperature alteration conditions of the zeolite to prehnite -pumpellyite facies (Kano et al, 1986;Akasaka et al, 1997;Nagashima et al, 2006). In this assemblage, prehnite occurs as an overgrowth phase on the Fe -rich pumpellyite (Kano et al, 1986;Akasaka et al, 1997), indicating later crystallization of prehnite than Fe -rich pumpellyite with decreasing fluid temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In the altered dolerite at Kouragahana, Mihonosekicho, Shimane Peninsula, prehnite (Nomura et al, 1984;Akasaka et al, 2003a) and Fe -rich pumpellyite (Nagashima et al, 2006) occur in cavities or veins. Veins from a few to tens of centimeters in width and cavities with diameters of about 15 cm occur.…”
Section: Occurrence Of Samplementioning
confidence: 99%
“…Moore et al (1985). (Artioli and Geiger, 1994;Akasaka et al, 1997;Artioli et al, 2003;Nagashima et al, 2006) , occupies the Y site. Cr -rich pumpellyite from Bisersk was named 'shuiskite'.…”
Section: Topological Relations Of Pumpellyite Sursassite Macfallitementioning
confidence: 99%